Understanding the impetus for major systems change: A multiple case study of decisions and non-decisions to reconfigure emergency and urgent care services. Issue 8 (August 2019) - McHugh, Sheena; Droog, E.; Foley, Conor; Boyce, M.; Healy, O.; Browne, J.P.
Highlights: Triggering events provide impetus and an obvious starting point for reconfiguration. Political influence is pervasive, shaping decisions and non-decisions about reconfiguration. Clinical leadership fosters local professional support and provides public reassurance. Reconfiguration should be incremental with sufficient lead-in time to plan and sell changes. Inconsistent implementation undermines public trust in the rationale for reconfiguration. Abstract: Objective: The optimal organisation of emergency and urgent care services (EUCS) is a perennial problem internationally. Similar to other countries, the Health Service Executive in Ireland pursued EUCS reconfiguration in response to quality and safety concerns, unsustainable costs and workforce issues. However, the implementation of reconfiguration has been inconsistent at a regional level. Our aim was to identify the factors that led to this inconsistency. Methods: Using a multiple case study design, six case study regions represented full, partial and little/no reconfiguration at emergency departments (EDs). Data from documents and key stakeholder interviews were analysed using a framework approach with cross-case analysis. Results: The impetus to reconfigure ED services was triggered by patient safety events, and to a lesser extent by having a region-specific plan and an obvious starting point for changes. However, the complexity of the next steps and political influence impeded reconfiguration in several regions. Implementation was more strategic in regions that reconfigured later, facilitated by clinical leadership and "lead-in time" to plan and sell changes. Conclusion: While the global shift towards centralisation of EUCS is driven by universal challenges, decisions about when, where and how much to implement are influenced by local drivers including context, people and politics. This can contribute to a public perception of inequity and distrust in proposals for major systems change.